Frequency of Vitamin D Deficiency in Pre-Eclamptic Women - Sabreena Abbas, Fouzia Shaikh, Farkhunda Khursheed, Romana Khan, Farhat Sultana, Ambreen Mughal, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To determine the frequency of vitamin D deficiency in pre-eclamptic women admit in tertiary care hospital of Sindh Pakistan. Study design: Cross sectional study. Place and duration of study: Department of Obstetrics & Gynaecology, Liaquat University of Medical & Health Sciences Hospital Hyderabad from 1st December 2020 to 30th May 2021 Methodology: One hundred and fifty seven women with pre-eclampsia after 20 weeks of gestation were included. Detailed medical and obstetrical history and physical examination was carried out. Urine sample (MSU) was sent for test of proteinuria and after the confirm diagnosis of pre-eclampsia, blood sample was taken and sent to laboratory for measurement of serum Vitamin D (25(OH) D) levels and patients was categorized as Vitamin D deficient (below 75nmol/L (or 30ng/ml) of serum/plasma 25(OH)D concentration) or sufficient on the basis of serum vitamin D levels. Results: The average age was 29.06±3.96 years. Frequency of vitamin D deficiency was found in 130(82.8%) patients while sufficiency was found in 27(17.2%) of pre-eclamptic women. Conclusion: Pre-eclamptic women had a higher frequency of vitamin D deficiency. It is suggested that pregnant women at risk of vitamin D deficiency can be protected from hypertensive disease during pregnancy by a simple step of vitamin D supplementation during pregnancy. Keywords: Hypertensive disorders, Vitamin D deficiency, Pre-eclamptic